"She can‘t help it, she was born that way": Adolescents' beliefs about the origins of homosexuality and sexual prejudice - S. Horn, Stacey; Heinze, Justin (Anales de Psicología / Annals of Psychology, 2011)
This paper examined differences in American adolescents‘ (n = 1069) beliefs about the origins of homosexuality and how these beliefs related to adolescents‘ judgments and reasoning about homosexuality, their comfort interacting with lesbian and gay peers, and their judgments and reasoning about the treatment of lesbian and gay peers. Using Latent Class Analysis four origins cluster profiles were determined (choice/early socialization, choice, socialization, and biological). Results provide evidence that adolescents endorsing socialization beliefs about the origins of homosexuality were more likely to evaluate homosexuality as wrong, least comfortable interacting with lesbian and gay peers, and least likely to evaluate exclusion and teasing a lesbian or gay peer as wrong. Conversely, adolescent endorsing biological beliefs were least likely to evaluation homosexuality as wrong, most comfortable interacting with lesbian and gay peers, and most likely to evaluate exclusion and teasing as wrong. Further, the results provide evidence that origins beliefs were also related to the type of reasoning (moral, conventional, personal) that adolescents bring to bear on these issues.